Analisis Pengaruh Profitabilitas, Ukuran Perusahaan, dan Kebijakan Utang Terhadap Nilai Perusahaan: Studi Empiris pada Property and Real Estate Company yang Terdaftar di Bursa Efek Indonesia - Fierlanda Sheren Ayundha Wardani; Cahyono, Yuli Tri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to test and analyze the influence of profitability, company size, and debt policy on firm value. This research was tested with a sample of 68 property and real estate companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. The sampling method uses purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The findings indicate that profitability, company size, and debt policy have a impact on firm value.